2019
DOI: 10.1016/j.meatsci.2019.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Post-processing feasibility of composite-layer 3D printed beef

Abstract: Post-processing feasibility studies the integrity of the designed internal and external structures of 3D printed products. This study examined the effect of infill density (50%, 75%, 100%) and fat content (0, 1, 2, 3 fat layers within a structure) on the post-processing physical changes and texture of lean meat-lard composite layer 3D printed meat products cooked sousvide. Data from raw and cooked samples were collected to determine cooking loss, shrinkage, moisture retention, fat retention, hardness, chewines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(46 citation statements)
references
References 30 publications
0
44
0
2
Order By: Relevance
“…The cooked samples maintained the structure with slight inward contraction in all the layers. It was observed that increasing the lard layers led to higher cooking loss, shrinkage, cohesiveness, lower fat retention, moisture retention, hardness, and chewiness, whereas increasing the infill density led to higher moisture retention with lower shrinkage and cohesiveness, resulting in higher hardness and chewiness [ 56 ].…”
Section: Processingmentioning
confidence: 99%
“…The cooked samples maintained the structure with slight inward contraction in all the layers. It was observed that increasing the lard layers led to higher cooking loss, shrinkage, cohesiveness, lower fat retention, moisture retention, hardness, and chewiness, whereas increasing the infill density led to higher moisture retention with lower shrinkage and cohesiveness, resulting in higher hardness and chewiness [ 56 ].…”
Section: Processingmentioning
confidence: 99%
“…Early application of 3D food printing focused more on the aesthetics and shape, with various readily available materials (e.g., chocolate, hazelnut cream, cream cheese) as raw material [ 1 , 2 , 3 ]. However, recent research utilizes 3D printing as a potential processing technology to deliver personalized healthy eating solutions by the use of a wide range of protein and/or dietary fibre-rich materials, such as oat and faba bean protein concentrates [ 4 ], meat [ 5 ], milk protein [ 6 ] and soy protein isolate [ 7 ], either as such or in combination with starch or other hydrocolloids. On the other hand, 3D printing could potentially be used for the delivery of micronutrients, antioxidants and probiotics [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers from the School of Agriculture and Food Sciences, the University of Queensland (Australia) studied an effect of infill density (50%, 75%, and 100%) in the rectangular prism (40x40x10 mm) filled with a meat composition and its fat content determined by the number of layers of minced lard (0, 1, 2, and 3 layers) in the structure of the 3D meat product on the parameters of final processing of meat products cooked by the sous-vide method [21].…”
Section: Possibilities Of 3d Printing In the Meat Industry (For Meat mentioning
confidence: 99%
“…The infill density did not influence the deviation from the product designed height, while an inverse relationship was found when the fat content was increased. This can be explained by the lower mass of the extruded lard layer compared to the mass of meat paste, as the lard layer was deposited by the nozzle with a smaller diameter (1 mm) and a lower density of fat (0.9 g/mL (FAO/WHO Food Standards Programme, 2001)) compared to a density of the meat paste (1.106 g/mL), which was extruded using the nozzle with a diameter of 2 mm [21].…”
Section: Possibilities Of 3d Printing In the Meat Industry (For Meat mentioning
confidence: 99%
See 1 more Smart Citation